Addiction Research Consortium: Losing and regaining control over drug intake (ReCoDe)—From trajectories to mechanisms and interventions. (20th December 2019) - Heinz, Andreas; Kiefer, Falk; Smolka, Michael N.; Endrass, Tanja; Beste, Christian; Beck, Anne; Liu, Shuyan; Genauck, Alexander; Romund, Lydia; Banaschewski, Tobias; Bermpohl, Felix; Deserno, Lorenz; et al.
Abstract: One of the major risk factors for global death and disability is alcohol, tobacco, and illicit drug use. While there is increasing knowledge with respect to individual factors promoting the initiation and maintenance of substance use disorders (SUDs), disease trajectories involved in losing and regaining control over drug intake (ReCoDe) are still not well described. Our newly formed German Collaborative Research Centre (CRC) on ReCoDe has an interdisciplinary approach funded by the German Research Foundation (DFG) with a 12‐year perspective. The main goals of our research consortium are (i) to identify triggers and modifying factors that longitudinally modulate the trajectories of losing and regaining control over drug consumption in real life, (ii) to study underlying behavioral, cognitive, and neurobiological mechanisms, and (iii) to implicate mechanism‐based interventions. These goals will be achieved by: (i) using mobile health (m‐health) tools to longitudinally monitor the effects of triggers (drug cues, stressors, and priming doses) and modify factors (eg, age, gender, physical activity, and cognitive control) on drug consumption patterns in real‐life conditions and in animal models of addiction; (ii) the identification and computational modeling of key mechanisms mediating the effects of such triggers and modifying factors on goal‐directed, habitual, and compulsive aspects of behavior from human studies and animal models; and (iii) developing and testing interventions that specifically target the underlying mechanisms for regaining control over drug intake. Abstract : The losing and regaining control over drug intake (ReCoDe) framework to study losing and regaining control over drug intake over a 12‐year perspective: Our 19 projects are divided into three research domains